ANALISIS KRITIS KONSEP KEPEMILIKAN HARTA DALAM ISLAM - Fitri Utami; Dini Maulana Lestari; Khaerusoalikhin Khaerusoalikhin (Institut Agama Islam Negeri Batusangkar, 2020)
Wealth or property is the esential thing which has a thighten relationship throug human life. Islam has already well organized regarding to wealth or property ownership. One of Islamic property ownership concepts is Ihrazul Mubahat which means free property ownership. However, is ihrazul mubahat concept appropriate if it is implemented in Indonesia? While as known as Indonesia has two resources of law, those are positive law and sharia law. The purpose of this article is to discuss deeply regarding to implementasion of ihrazul mubahah concept in Indonesia, and this is kind of descriptive qualitative method research throgh library research approach. The result of this research revealed that in Islamic property and ownership specifically ihrazul mubahat concept needs such a regulation in the term of Islamic law regarding to enrole of ihrazul mubahah concept properly, thus it can be adapted into Indonesia’s law system.